Quantitative Analyses of Schizophrenia-Associated Metabolites in Serum: Serum D-Lactate Levels Are Negatively Correlated with Gamma-Glutamylcysteine in Medicated Schizophrenia Patients - Fukushima, Takeshi; Iizuka, Hideaki; Yokota, Ayaka; Suzuki, Takehiro; Ohno, Chihiro; Kono, Yumiko; Nishikiori, Minami; Seki, Ayaka; Ichiba, Hideaki; Watanabe, Yoshinori; Hongo, Seiji; Utsunomiya, Mamoru; et al. (PloS one, 2014)
The serum levels of several metabolites are significantly altered in schizophrenia patients. In this study, we performed a targeted analysis of 34 candidate metabolites in schizophrenia patients (n = 25) and compared them with those in age- and gender-matched healthy subjects (n = 27). Orthogonal partial least square-discriminant analysis revealed that complete separation between controls and patients was achieved based on these metabolites. We found that the levels of γ-glutamylcysteine (γ-GluCys), linoleic acid, arachidonic acid, D-serine, 3-hydroxybutyrate, glutathione (GSH), 5-hydroxytryptamine, threonine, and tyrosine were significantly lower, while D-lactate, tryptophan, kynurenine, and glutamate levels were significantly higher in schizophrenia patients compared to controls. Using receiver operating characteristics (ROC) curve analysis, the sensitivity, specificity, and the area under curve of γ-GluCys, a precursor of GSH, and D-lactate, a terminal metabolite of methylglyoxal, were 88.00%, 81.48%, and 0.8874, and 88.00%, 77.78%, and 0.8415, respectively. In addition, serum levels of D-lactate were negatively correlated with γ-GluCys levels in patients, but not in controls. The present results suggest that oxidative stress-induced damage may be involved in the pathogenesis of schizophrenia.